2019
DOI: 10.1017/s0007114519001429
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in postprandial responses to different dairy products on lipoprotein subclasses: a randomised controlled cross-over trial

Abstract: Men have earlier first-time event of CHD and higher postprandial TAG response compared with women. The aim of this exploratory sub-study was to investigate if intake of meals with the same amount of fat from different dairy products affects postprandial lipoprotein subclasses differently in healthy women and men. A total of thirty-three women and fourteen men were recruited to a randomised controlled cross-over study with four dairy meals consisting of butter, cheese, whipped cream or sour cream, corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…In addition, here we report for the first time significant effects of the Exercise treatment on blood 0 Particle concentration of HDL-P subclasses and HDL-C increase during gestation and decline after delivery, to levels slightly elevated at 3 months postpartum compared to 1-3 years postpartum (37). Baseline concentrations of HDL-P subclasses in our population were similar or slightly elevated compared to non-pregnant, non-lactating women of the same age group (38). Thus, a decline in the concentration of HDL subclasses was likely ongoing at baseline in our study.…”
Section: Discussionsupporting
confidence: 51%
“…In addition, here we report for the first time significant effects of the Exercise treatment on blood 0 Particle concentration of HDL-P subclasses and HDL-C increase during gestation and decline after delivery, to levels slightly elevated at 3 months postpartum compared to 1-3 years postpartum (37). Baseline concentrations of HDL-P subclasses in our population were similar or slightly elevated compared to non-pregnant, non-lactating women of the same age group (38). Thus, a decline in the concentration of HDL subclasses was likely ongoing at baseline in our study.…”
Section: Discussionsupporting
confidence: 51%
“…However, over the past 10 years a consensus of studies has built which has questioned the assumption of adverse effects for dairy-origin SFAs for both CV and T2D outcomes. Notably, it is no longer adequate to consider nutrients in isolation, with evidence that the complex matrix of a food may be equally or more important than the fatty acid content and composition alone when predicting cardiometabolic risk (3,10,11). It has been proposed that in a complex dairy food such as cheese, for example, the effect of SFAs on blood lipids and disease risk may be counterbalanced by the content of protein, calcium, or other dietary components (23,129).…”
Section: Dairy and The Saturated Fat Controversymentioning
confidence: 99%
“…There is also a new but growing consensus that the matrix of a whole-fat food such as dairy may be more important than the content and composition of component isolated fatty acids. Such that food-based rather than nutrient-based recommendations should be developed for CV health (3,10,11). It is notable however that the predominance of this evidence is obtained from observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional analyses have shown less atherogenic lipoprotein subfraction profiles characterized by smallersized very-low-density lipoproteins (VLDLs), larger-sized LDLs, and/or larger-sized HDLs in females relative to males (16, [34][35][36][37][38][39]. Studies have overall reported lower levels of large/medium VLDLs and higher concentrations of large/medium HDLs in females compared with males (16, [36][37][38]40), as well as lower TAGs and higher HDL cholesterol (HDL-C) (14,16,(34)(35)(36)(37)(38)(40)(41)(42)(43)(44)(45)(46)(47)(48), while the sex differences were more variable in other lipoprotein subfractions and lipids.…”
Section: Introductionmentioning
confidence: 99%